A Case Report of Maxillary Sinus Mucocele and Its Endoscopic Therapy - Mohammad Shayani Nasab (پزشکی بالینی ابن سینا, 2004)
Maxillary sinus mucocele is very rare in the Para nasal sinuses and sinus surgery e.g. Caldwell-luk surgery is the most common its etiology and other causes are congenital ,mucosal retention , inflammatory , infectious and post traumatic.